2018
DOI: 10.1002/cctc.201801742
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Surface Structure of Silicon Carbide Support for Copper Catalyzed Ethanol Dehydrogenation

Abstract: The production of acetaldehyde through biomass‐derived ethanol dehydrogenation is a sustainable alternative compared to the fossil‐feedstock based process, for which Cu‐based catalysts are considered to be the most efficient. Herein, we modified the surface of silicon carbide (SiC) to alter the properties of the interface from SiO2‐rich to C‐rich, and we prepared a series of Cu‐supported catalysts (Cu/SiC, Cu/SiO2/SiC, and Cu/C/SiC) with the aim of insight into the effect of the interface structure and composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 39 publications
2
29
1
Order By: Relevance
“…This discrepancy might be due to the ultra-high vacuum reaction conditions of the TAP experiments in this work. shown in Figure 10b, is in contrast to the experimental results of many papers in the literature working with Cu catalysts, which report on high selectivities towards acetaldehyde of in parts 100% [17,19,21,23,25]. This discrepancy might be due to the ultra-high vacuum reaction conditions of the TAP experiments in this work.…”
Section: Experiments With Cu/ccontrasting
confidence: 99%
See 1 more Smart Citation
“…This discrepancy might be due to the ultra-high vacuum reaction conditions of the TAP experiments in this work. shown in Figure 10b, is in contrast to the experimental results of many papers in the literature working with Cu catalysts, which report on high selectivities towards acetaldehyde of in parts 100% [17,19,21,23,25]. This discrepancy might be due to the ultra-high vacuum reaction conditions of the TAP experiments in this work.…”
Section: Experiments With Cu/ccontrasting
confidence: 99%
“…Many research groups have found Cu catalysts to be highly active for ethanol dehydrogenation, revealing selectivities towards acetaldehyde of almost 100% in some cases [16][17][18][19][20][21][22][23][24][25]. A positive effect is reported when the Cu content increased in the range of 1-5 wt % [26].…”
Section: N2 Sorptionmentioning
confidence: 99%
“…By these treatments, the residual carbon and SiO 2 generated on the surface of SiC NPs were removed. The in situ formation of atomic carbon layers on the surface of SiC NPs was conducted by dry etching with CCl 4 gas where surface silica atoms were selectively etched . Such a process is schematically shown in Scheme S1 (Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…A good support should ensure a suitable dispersion of the Cu active phase, possibly stabilizing it during the high-temperature reaction [28]. Inert SiO2 [11,12], mesoporous carbon [13], silicon carbide [29], and carbon layer-coated SiO2 [15] as well as rice husk ash [17] have already been tested as candidate supports.…”
Section: Introductionmentioning
confidence: 99%